Adaptable Project Management : a combination of Agile and Project Management for All (PM4A) - Bentley, Colin (IT Governance Publishing, 2020)
Adaptable Project Management - A combination of Agile and Project Management for All (PM4A) dispels the myth that Agile approaches to project management can only be used for software development. It gives advice on how to combine the benefits of Agile and waterfall project management methodologies for successful project implementation.